2017
DOI: 10.1177/0013916517710077
|View full text |Cite
|
Sign up to set email alerts
|

The Soothing Sea: A Virtual Coastal Walk Can Reduce Experienced and Recollected Pain

Abstract: Virtual reality (VR) distraction has become increasingly available in health care contexts and is used in acute pain management. However, there has been no systematic exploration of the importance of the content of VR environments. Two studies tested how interacting with nature VR influenced experienced and recollected pain after 1 week. Study 1 (n = 85) used a laboratory pain task (cold pressor), whereas Study 2 (n = 70) was a randomized controlled trial with patients undergoing dental treatment. In Study 1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 58 publications
6
76
1
1
Order By: Relevance
“…However, the results of previous VR studies are confounded by motion sickness, inadequate controls, or limited sensory inputs from the real nature treatment. Building on previous research that has demonstrated nature videos in VR generally provide beneficial effects (White et al, 2018) and that these effects are superior to those effects elicited from videos of built environments in VR (van den Berg et al, 2016;Tanja-Dijkstra et al, 2018;Hedblom et al, 2019), this is the first study to compare outdoor nature with virtual nature that has attempted to overcome these previous limitations while also adjusting for a range of individual differences related to nature and VR. We compared changes in mood, restorativeness, and physiological arousal after 6 min of exposure to outdoor nature, VR nature, and an indoor control in a sample of healthy undergraduate students.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the results of previous VR studies are confounded by motion sickness, inadequate controls, or limited sensory inputs from the real nature treatment. Building on previous research that has demonstrated nature videos in VR generally provide beneficial effects (White et al, 2018) and that these effects are superior to those effects elicited from videos of built environments in VR (van den Berg et al, 2016;Tanja-Dijkstra et al, 2018;Hedblom et al, 2019), this is the first study to compare outdoor nature with virtual nature that has attempted to overcome these previous limitations while also adjusting for a range of individual differences related to nature and VR. We compared changes in mood, restorativeness, and physiological arousal after 6 min of exposure to outdoor nature, VR nature, and an indoor control in a sample of healthy undergraduate students.…”
Section: Discussionmentioning
confidence: 99%
“…Widespread interest and research activity in VR technology, however, began much earlier. The Ultimate Display was demonstrated by Sutherland (1965) to track the head of a user and adjusted the simple graphics on a wearable display, thereby giving the illusion of a virtual environment that surrounds the user. Popular and commercial interest in VR soared in the 1980s and then diminished across the 1990s, mainly because the technology was too costly or ineffective due to hardware limitations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several other studies that demonstrate a sedation or analgesic sparing effect of IVR [7][8][9][10][11]. Further efforts have also been made to commercialize IVR, with little high-quality evidence of effectiveness [12].…”
Section: Introductionmentioning
confidence: 99%
“…Those randomized to either type of VR reported reduced experienced and recollected pain compared with no VR. Furthermore, the content of the VR mattered: coastal nature VR was reportedly better for pain reduction than urban VR (Tanja-Dijkstra et al, 2018).…”
Section: Bathing Waters Quality and Trendsmentioning
confidence: 99%